Batman : the Dark Knight returns - Miller, Frank, 1957-; Finger, Bill, 1914-1974.; Kane, Bob.; Shuster, Joe, 1914-1992.; Siegel, Jerry, 1914-1996. (Burbank, CA : DC Comics, 2016)
Ten years after his retirement, a troubled Batman returns to the streets, evening the score with criminals in an increasingly violent manner, which brings trouble from the police and a gang called the Mutants and a conflict with Superman.
"Batman created by Bob Kane with Bill Finger."
"Originally published in single magazine form as Batman: the Dark Knight 1-4"--T.p. verso.
"Superman created by Jerry Siegel & Joe Shuster."
Young Adult.
Young Adult
Keywords: Batman, -- (Fictitious character -- Comic books, strips, etc. -- Fiction; Batman, -- (Fictitious character -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Superheroes -- Comic books, strips, etc -- Fiction; COMICS & GRAPHIC NOVELS / Superheroes; Good and evil -- Comic books, strips, etc -- Fiction; Superheroes -- Comic books, strips, etc -- Fiction; Detective and mystery comics; Graphic novels; Superhero comics